The Adoption of Indirect Instruments of Monetary Policy - Balino, Tomas; Alexander, William; Enoch, Charles (Washington, D.C. : International Monetary Fund, 1995)
This paper examines the experience of implementing indirect instruments of monetary policy. The experiences of country studies illustrate the variety of circumstances under which indirect instruments of monetary policy have been introduced. Case Studies are presented for Chile, Egypt, Ghana, Indonesia, Mexico, New Zealand, and Poland.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet